ORTOGRAFI DAN UNIFIKASI AL-QUR’AN: Studi Buku Rekonstruksi Sejarah Al-Quran Karya Taufiq Adnan Amal - Zahro, Latifatuz; Lahuddin, Mukhlishina; Nabila, Munadhil (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Orthography refers to the description of the sounds of language used by humans in the form of writing or symbols. The difference and diversity of readings of the Qur'an that exist in society is the impact of orthography that triggers the emergence of efforts to classify qiraat and qurra' from each community. The orthography and unification of the Qur'an are important to discuss so that the readings in the Qur'an that are currently circulating are not in doubt about their authenticity. This study uses the book Reconstruction of the History of the Qur'an by Taufik Adnan Amal as the basis. It will also discuss further the development of orthography and unification, especially in the early days of orthography and unification. Abstrak Ortografi merujuk pada gambaran bunyi bahasa yang digunakan oleh manusia dalam bentuk tulisan atau lambang. Perbedaan serta keragaman bacaan al-Qur’an yang ada pada masyarakat adalah dampak dari ortografi yang memicu munculnya usaha pengklasifikasian qiraat dan qurra’ dari masing-masing masyarakat. Ortografi dan unifikasi al-Qur’an penting untuk dibahas supaya bacaan dalam al-Qura’an yang beredar sekarang tidak diragukan keauntentikasinya. Penelitian ini menggunakan buku Rekonstruksi Sejarah Al-Qur’an karya Taufik Adnan Amal sebagai landasannya. Serta didalamnya akan dibahas lebih lanjut mengenai perkembangan ortografi dan unifikasi terutama pada masa awal adanya ortografi dan unifikasi.